Increase in mechanical load and pro-fibrotic stimulation leads to fibrotic and hypertrophic remodeling in porcine living myocardial slices - Bentele, Marco; Linke, Sophie; Neumüller, Susanne; Korte, Andrea; Gietz, Anika; Just, Annette; Stucki-Koch, Angelika; Pfanne, Angelika; Liu, Junqing; Zhao, Jiahao; Schwennen, Cornelia; Homann, Christian; et al. (Scientific reports, 2025)
Heart failure (HF) is a growing global health concern, driven by factors such as increased mechanical load of the heart muscle tissue. This pathogenic condition is the result of remodeling processes, partially mediated by the cytokine transforming growth factor β (TGF- β1), with progressive deposition of extracellular matrix within the myocardium that ultimately increases tissue stiffness. To elucidate early cellular and molecular processes underlying cardiac remodeling, translational experimental models are required. Living myocardial slices (LMS) represent a promising ex vivo model with preserved multicellularity, and physiology. In this study, we developed a disease model with hypertrophic and fibrotic features in porcine LMS. For this, LMS were prepared from porcine left ventricular tissue and cultured under mechanical overload with or without TGF-β1 stimulation. LMS cultured under overload showed reduced contractile performance, while adding TGF- β1 resulted in higher collagen deposition in the tissue, increase in secretion levels of pro-fibrotic miR-21 into the culture supernatant and increased expression of pro-fibrotic and hypertrophic marker genes. Our findings demonstrate early fibrotic changes in pig LMS induced by both mechanical and chemical stimulations. This ex vivo model could provide valuable insights into the early changes in heart failure pathogenesis and could be utilized as a screening platform to validate treatment strategies targeting cardiac remodeling.